AN ANALYSIS OF THE ASSOCIATION BETWEEN THE USE OF ELECTRONIC NURSING DOCUMENTATION AND THE QUALITY OF EFFECTIVE COMMUNICATION AMONG NURSES IN HOSPITAL SETTINGS - Made Indra Ayu Astarini; Ira Ayu Maryuti; Kristina Pae (Nurse and Holistic Care, 2026)
Background: All healthcare services, including hospitals, are required to implement electronic documentation. The purpose is to facilitate access and support clinical decision-making related to patients. Challenges arise when nurses perform electronic documentation, as they may become overly focused on documentation tasks and fail to engage in effective communication with other nurses. Objective: This study aimed to explain the relationship between the use of electronic documentation and the quality of effective communication among nurses.Methods: This study employed a cross-sectional research design. The population consisted of all nurses in inpatient ward who used electronic documentation at Hospital X in Surabaya. The sample size was 122 respondents who participated within one week of data collection. The sampling technique used was total sampling. The independent variable was the use of electronic documentation, while the dependent variable was effective communication among nurses.Results: The results showed that the majority of respondents were demonstrated good acceptance of electronic documentation use (117; 95.9%) and had good effective communication skills (100; 82%). Cross-tabulation analysis also showed that 98 respondents had both good acceptance of electronic documentation and good effective communication skills. The analysis indicated a significant relationship between the acceptance of electronic documentation use and effective communication skills (p = 0.012; p < α) with a correlation coefficient of r = 0.226. The r value indicates a positive relationship between the two variables.Conclusion: The correlation coefficient indicates a positive association, suggesting that higher acceptance of electronic documentation is associated with better effective communication among nurses.